1994
DOI: 10.5271/sjweh.1397
|View full text |Cite
|
Sign up to set email alerts
|

Internal load of aluminum and the central nervous system function of aluminum welders.

Abstract: Internal load of aluminum and the central nervous system function of aluminum welders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 11 publications
(16 reference statements)
6
32
0
Order By: Relevance
“…Morris water maze is regarded as a typical instrument to evaluate cognitive abilities of rodents. The hidden platform acquisition could reflect the function of hippocampus (Morris et al, 1986), and hippocampus-dependent spatial learning and memory of animals are frequently investigated in the water maze (Astur et al, 2004), It was reported that visual spatial perception ability, psychomotor ability, short-term memory and learning ability were subject to a certain degree of damage in Al-related workers (Bast-Pettersen et al, 1994;Hanninen et al, 1994;Riihimaki, 2000). In addition, a survey revealed that the children's intelligence near the Al plant was significantly lower than that of other children at the same age (Buchta et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Morris water maze is regarded as a typical instrument to evaluate cognitive abilities of rodents. The hidden platform acquisition could reflect the function of hippocampus (Morris et al, 1986), and hippocampus-dependent spatial learning and memory of animals are frequently investigated in the water maze (Astur et al, 2004), It was reported that visual spatial perception ability, psychomotor ability, short-term memory and learning ability were subject to a certain degree of damage in Al-related workers (Bast-Pettersen et al, 1994;Hanninen et al, 1994;Riihimaki, 2000). In addition, a survey revealed that the children's intelligence near the Al plant was significantly lower than that of other children at the same age (Buchta et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Aluminum welders with about 13 years of full-time employment reported concentration difficulties and depression twice as frequently as welders of mild steel (30). Our previous study of 17 MIG welders with about 4 years of exposure and moderately raised S-A1 (mean 0.21 pmol/l) and U-A1 (mean 2.8 pmolll) concentrations suggested slight dose-related impairments in memory functions, learning, and attention, as well as in characteristic slowing of the EEG in the frontal region (31). A more recent study of aluminum welders whose median (maximum) blood and U-A1 levels were 0.11 (SD 1.0) and 0.8 (SD 9.4) pmolll, respectively, showed exposure-related decrements in the motor function of the hands; the welders reported more fatigue at the time of the test (48).…”
Section: Discussionmentioning
confidence: 99%
“…The test battery with 12 tests used in our previous aluminum study (31) was complemented by a more comprehensive selection of tests for attention and memory. Table 1 shows the methods used in this study.…”
Section: Lveuropsychological Test Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The test methods were selected on the basis of ®ndings from previous studies among aluminum-exposed workers, where the main ®ndings include neuropsychiatric symptoms, impaired motor function and longer reaction times [BastPettersen et al, 1994;Sim et al, 1997;Sjo Ègren et al, 1990;Ha Ènninen et al, 1994;.…”
Section: Introductionmentioning
confidence: 99%